Avaliação da aprendizagem e sequência didática no ensino de produção escrita: aspectos formativos - Ribeiro, Débora de Lima (2014)
The teaching practice should seek to improve the teaching and learning process as well as the professionals should look for a quality education. And for this it is necessary to constantly review their ways of teaching educational content analyzing their efficiency. In this sense, we realize that new methodological strategies for teaching writing production through the use of textual genres and execution of didactic sequences are tools that can help teachers in developing their teaching practice. The correct treatment of linguistic concepts and their influence on education as well as knowledge of which practices are best suited to work the various genres in the classroom are very important, but it is not always easy to do it, because there are so many doubts. However, with continued investment in about the training concepts and strategies available, it is possible to assist educators in their formative process so that they can make improvements in the teaching and learning process. In this work we discussed the teaching practice and the teaching of writing production mediated by sequences didactic and formative assessment, with the conception of interactionism Sociodiscursivo, in order to promote actions that can contribute to the development of writing skills of students through work with didactic sequences, developed in modules that arise from assessments previously made and during the process, and which facilitate and guide the necessary interventions. Besides the theoretical context, the paper presents a content analysis that aims to enlighten educators about the development of teaching strategies.